Double Shift (Reality/Example) in the Short Story Collection "A Heart ... Mentally Deranged"by "ZinedineBoomerzouk" - Nouadria, Karima (Milev Journal of Research and Studies, 2023)
ZinedineBoumerzouk is a creative experience - given her young age in the field of a very short story - exceptional in her awareness, and in her ability to listen and follow, looking for a virgin existence in which the self is liberated from the violence of negative forces, and is evidenced - as the group presenter Saeed Butajin sees - “the decay Judgment, relationships, broken buildings, and the fragmentation of man, who has turned into a wreck, scattered, and a great deformation. " Applying to him, this paper aims to understand the various concerns that his collection of short stories bears, "A Heart ... a Mentally Conqueror", inquiring and examining titles, places, characters, and the various relationships that bind them to the social and psychological context that formed them